Personality and contextual correlates of parenting self-efficacy among mothers and fathers of Croatian adolescents - Keresteš, Gordana (Array, 2009)
Parenting self-efficacy is a construct which importance has recently been highlighted in the literature on parenting. In accordance with Bandurian tradition, it has been most often defined as a self-perception of one's ability to perform competently and effectively in the parental role. Research on parenting self-efficacy is in its infancy, and little is known about the sources and correlates of parenting self-efficacy, as well as about its effects on parenting behavior and child development. The aim of the present study was to investigate personality and contextual correlates of parenting self-efficacy among 812 pairs of mothers and fathers of Croatian young adolescents (age 10 to 15 years). The average age of mothers was 39, and of fathers 42 years. Socio-demographic factors (parental age, education, and employment status ; number of children in the family), big five personality traits, and contextual sources of stress and support (agreement between spouses on child-rearing, marital satisfaction, and social support) were analyzed as possible predictors of parenting self-efficacy. Hierarchical regression analyses revealed that contextual and personality factors explained 27 percents of maternal and 31 percent of paternal self-efficacy variance. The most important predictors of both maternal and paternal self-efficacy were neuroticism, conscientiousness, agreement between spouses on child-rearing, and perceived social support. In addition, among fathers, significant predictors of self-efficacy were marital satisfaction and education, while among mothers significant predictor of self-efficacy was openness to experience. Higher parental self-efficacy was related to lower neuroticism, higher conscientiousness, and higher openness to experience (for mothers only), as well as to higher agreement between spouses on child-rearing, higher marital satisfaction (for fathers only), and higher education (for fathers only).